2011
DOI: 10.1093/mp/ssr023
|View full text |Cite
|
Sign up to set email alerts
|

COPPER AMINE OXIDASE1 (CuAO1) of Arabidopsis thaliana Contributes to Abscisic Acid-and Polyamine-Induced Nitric Oxide Biosynthesis and Abscisic Acid Signal Transduction

Abstract: Polyamines (PA), polyamine oxidases, copper amine oxidases, and nitric oxide (NO) play important roles in physiology and stress responses in plants. NO biosynthesis as a result of catabolism of PA by polyamine oxidases and copper amine oxidases may explain in part PA-mediated responses. Involvement of a copper amine oxidase gene, COPPER AMINE OXIDASE1 (CuAO1), of Arabidopsis was tested for its role in stress responses using the knockouts cuao1-1 and cuao1-2. PA-induced and ABA-induced NO production investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 70 publications
4
88
0
1
Order By: Relevance
“…In contrast, exogenous polyamines, especially putrescine, induced NO generation in soybean [50]. Reduced NO release was observed in copper amino oxidase 1 knock-out Arabidopsis [51]. These results suggest that DAO might be involved in Page 13 of 33 A c c e p t e d M a n u s c r i p t 13 NO biosynthesis induced by polyamines.…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, exogenous polyamines, especially putrescine, induced NO generation in soybean [50]. Reduced NO release was observed in copper amino oxidase 1 knock-out Arabidopsis [51]. These results suggest that DAO might be involved in Page 13 of 33 A c c e p t e d M a n u s c r i p t 13 NO biosynthesis induced by polyamines.…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 92%
“…As Fe-superoxide-dismutase, dehydroascorbate reductase and monodehydroascorbate reductase are also polyamine-induced S-nitrosylation target proteins, NO-modulated S-nitrosylation is also a possible link between polyamines and stress responses [51]. The mode of action by which polyamines affect S-nitrosylation may differ for individual polyamines [55].…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to low temperature induces oxidative and nitrosative stress thereby promoting NO synthesis [119], which serves as a potential link between PA and ABA to induce stress responses in plants [120]. Literature indicated extensive cross talk among NO, ABA, PAs, and H 2 O 2 to modulate various physiological and stress responses under low temperature conditions [110,121].…”
Section: No-phytohormone Cross Talk Under Temperature Stressmentioning
confidence: 99%
“…NO has emerged as a key mediator of plant defense responses, and it is known that Spm and Spd are potent NO inducers (Tun et al, 2006;Wimalasekera et al, 2011a). Although further studies are needed to determine the NO generation mechanism in disease resistance, it has been reported that a knockout mutant of CuAO1, one of the AO genes in Arabidopsis, showed an impaired PA-induced NO release (Wimalasekera et al, 2011b).…”
Section: Protein-protein Interactionsmentioning
confidence: 99%